The perspective of new public management in the management of regional land and building assets - Nuzlan Botutihe; Srihandyani Suprapto (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2026)
This study examines the application of New Public Management (NPM) principles in the management of regional assets, particularly land and building assets, within the Gorontalo City Government. A descriptive qualitative approach was employed to explore the challenges and opportunities associated with implementing NPM principles, including performance standards, an emphasis on outputs and outcomes, professional management practices, the adoption of private-sector management styles, and the utilization of technology. Data were collected through in-depth interviews with government officials and asset management personnel, as well as through document analysis. The findings indicate that, although there is considerable potential to improve efficiency and effectiveness in regional asset management, significant challenges remain, particularly administrative disorganization and a relatively low level of professionalism among personnel. This study therefore recommends strengthening the accountability system, enhancing human resource capacity, and promoting the implementation of digital-based technologies to support more effective regional asset management.